2023
DOI: 10.1002/tox.23785
|View full text |Cite
|
Sign up to set email alerts
|

Antrodia camphorata and coenzyme Q0, a novel quinone derivative of Antrodia camphorata, impede HIF‐1α and epithelial‐mesenchymal transition/metastasis in human glioblastoma cells

Abstract: Antrodia camphorata (AC) and Coenzyme Q0 (CoQ0), a novel quinone derivative of AC, exhibits antitumor activities. The present study evaluated EMT/metastasis inhibition and autophagy induction aspects of AC and CoQ0 in human glioblastoma (GBM8401) cells. Our findings revealed that AC treatment (0–150 μg/mL) hindered tumor cell proliferation and migration/invasion in GBM8401 cells. Notably, AC treatment inhibited HIF‐1α and EMT by upregulating epithelial marker protein E‐cadherin while downregulating mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
1
0
1
Order By: Relevance
“… 38 Autophagy can also reverse EMT by reducing key proteins, such as SNAIL, SLUG, and TWIST in human glioblastoma cells. 39 To date, several studies have demonstrated that tumor cells can use EMT or autophagy in response to microenvironmental stress, that EMT and autophagy negatively regulate each other and that they are capable of interconversion. 40 , 41 In this study, we confirmed that OVOL2-mediated autophagy is associated with EMT in LUAD cells.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Autophagy can also reverse EMT by reducing key proteins, such as SNAIL, SLUG, and TWIST in human glioblastoma cells. 39 To date, several studies have demonstrated that tumor cells can use EMT or autophagy in response to microenvironmental stress, that EMT and autophagy negatively regulate each other and that they are capable of interconversion. 40 , 41 In this study, we confirmed that OVOL2-mediated autophagy is associated with EMT in LUAD cells.…”
Section: Discussionmentioning
confidence: 99%
“…Matrigel invasion chambers (BD Biosciences, MI, USA) were used to assess cell invasion following previously standardized procedures 26 . For invasion assay, 10 μL of Matrigel (25 mg/50 mL) were coated onto the 8-μm polycarbonate membrane filters, and then the cells (2 × 10 4 cells/well in 12-well plates) were seeded onto the Matrigel-treated filter in 200 μL of CoQ 0 (0-7.5 μM) for 24 h deprived of serum.…”
Section: Methodsmentioning
confidence: 99%
“…Antrodia c. індукувала апоптоз клітинної лінії MDA-MB-231 раку молочної залози in vitro та у мишей in vivo [33], разом з її похідним коензим Q 0 , препарати перешкоджали проліферації клітин гліобластоми GBM8401, їх міграції, інвазії, інгібували метастазування, індукували апоптоз та аутофагію [34]. У дослідженнях Yang та ін.…”
Section: результати та їх обговоренняunclassified